2012
DOI: 10.1177/1354068811436067
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the effects of interest-group endorsements on poorly aligned partisans in the 2008 presidential election

Abstract: In this article, we test the effects of interest group endorsements on potential voters in the 2008 presidential election. Specifically, we use a posttest-only, multiple control group experiment (N = 701) to examine how real-world endorsements affect citizens. We find that endorsements have profound effects on some voters. Specifically, we find that interest-group endorsements profoundly affect the candidate evaluations and stated voting preferences of potential voters who are what we call ‘poorly aligned’ – t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In fact, a few earlier studies found a cueing effect for interest groups (Lupia ; Arceneaux & Kolodny ; Neddenriep & Nownes ). These studies, however, did not distinguish between the impact of the source cue and the argument transmitted by groups.…”
Section: Interest Group Influence On Public Opinionmentioning
confidence: 95%
See 2 more Smart Citations
“…In fact, a few earlier studies found a cueing effect for interest groups (Lupia ; Arceneaux & Kolodny ; Neddenriep & Nownes ). These studies, however, did not distinguish between the impact of the source cue and the argument transmitted by groups.…”
Section: Interest Group Influence On Public Opinionmentioning
confidence: 95%
“…In fact, Arceneaux and Kolodny (: 759) explicitly state that their study design does not allow them to distinguish between the effect of the source cue and the message transmitted by the source. Similarly, in their study of the effect of interest group endorsements of presidential candidates, Neddenriep and Nownes () confronted their subjects with interest group endorsements that also contained information about the candidates’ stance on abortion.…”
Section: Interest Group Influence On Public Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Financial CHOICE Act of 2017 Allows banks of sufficient size to take additional risk, and limits the power of the 2009)'s and Neddenriep and Nownes (2014) studies of the effects of endorsements by abortion groups, although these studies also give subjects additional information beyond the SIGs' ratings, making it difficult to disentangle the impact of the SIGs' rating or endorsement.…”
Section: Club For Growthmentioning
confidence: 99%
“…Often, ads feature a prominent celebrity endorser asking that voters take action, such as voting for a particular candidate or signing a petition. Because endorsements—especially those by celebrities—are particularly persuasive (Neddenriep and Nownes 2014), we expect that ads featuring calls to action are related positively to the use of endorsements.…”
Section: Which Factors Predict Use Of Endorsements In Politics?mentioning
confidence: 99%